223k views
4 votes
(cosysin2x)dx+(cos^2y-cos^2
x)dy=0​

User Cord
by
5.1k points

1 Answer

2 votes


(cos \: y \: sin \: 2x)dx + ( {cos}^(2) y - {cos}^(2) x)dy = 0

It is of the form:-

M(x,y)dx+N(x,y)dy=0

So here,


M = (cos \: y \: sin \: 2x),N = ( {cos}^(2) y - {cos}^(2) - x)


\therefore{ \displaystyle{ \frac{ {\partial}M}{ {\partial}y} = - sin \: y \: sin \: 2x}}


N = {cos}^(2) y - {cos}^(2) x \implies \displaystyle{ \frac{{ \partial}N}{ \partial x} }


= - 2( - sin(x)cos(x)) = sin(2x)

So,


\large{ ( ( \partial M)/( \partial y) - ( \partial N)/( \partial x) )/(M) }


= ( - sin \: y \: sin \: 2x)/(cos \: y \: sin \: 2x)


= - ( sin \: 2x(1 + sin \: y))/(cos \: y \: sin \: 2x)


= - (sec \: y \: + \: tan \: y) = - g(y)


I.F. = {e}^( -\int g(y)dy)


= {e}^( \int (sec \: y \: + tan \: y)dy)


= {e}^( ln(sec \: y \: + tan \: y) + ln(sec \: y) )

Now,


cos \: y \: sin \: 2x \: sec \: y \: (sec \: y \: + tan \: y)dx + (co {s}^(2)y - {cos}^(2) x)sec \: y \: (sec \: y \: + tan \: y)dy = 0


= sin \: 2x(sec \: y \: + tan \: y)dx + (co {s}^(2) x)( {sec}^(2) y + sec \: y \: tan \: y)dy = 0


= sin \: 2x(sec \: y + tan \: y)dx + (1 - {sec}^(2) y \: {cos}^(2) x + sin \: y \: - {cos}^(2) x \: sec \: y \: tan \: y)dy = 0

So,the solution now is,


\displaystyle{\int_((y \: const))Mdx + \int(terms \: of \: \: N \: not \: containing \: x)dy = C}


\int \: sin \: 2x(sec \: y \: + tan \: y)dx + \int (1 + sin \: y)dy = C


- (1)/(2) cos \: 2x(sec \: y \: + tan \: y) + y = c - cos \: y

User Chiramisu
by
5.3k points